2022
DOI: 10.36096/brss.v3i4.276
|View full text |Cite
|
Sign up to set email alerts
|

Mediating role of trust in the relationship between public governance quality and tax compliance

Abstract: This paper examined the mediating role of trust in government on the influence of public governance quality indicators (accountability, political stability, government effectiveness, regulatory quality, rule of law, and control of corruption) on tax compliance in Africa. Cross-country data obtained from 38 African countries for 2015 was used and analyzed using Ordinary Least Squares (OLS) regression analysis. The study found that accountability, political stability, control of corruption, and trust have a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Alm et al also found that trust in government as well as national pride exerts a positive effect on tax compliance. Several recent results (e.g., Korgaonkar, 2022; Masud et al., 2021; Oladele et al., 2020) are consistent with the findings of Alm et al…”
Section: Literaturesupporting
confidence: 79%
“…Alm et al also found that trust in government as well as national pride exerts a positive effect on tax compliance. Several recent results (e.g., Korgaonkar, 2022; Masud et al., 2021; Oladele et al., 2020) are consistent with the findings of Alm et al…”
Section: Literaturesupporting
confidence: 79%